2021
DOI: 10.1186/s12915-021-01101-5
|View full text |Cite
|
Sign up to set email alerts
|

Starvation-induced cell fusion and heterokaryosis frequently escape imperfect allorecognition systems in an asexual fungal pathogen

Abstract: Background Asexual fungi include important pathogens of plants and other organisms, and their effective management requires understanding of their evolutionary dynamics. Genetic recombination is critical for adaptability and could be achieved via heterokaryosis — the co-existence of genetically different nuclei in a cell resulting from fusion of non-self spores or hyphae — and the parasexual cycle in the absence of sexual reproduction. Fusion between different strains and establishment of viabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 96 publications
(169 reference statements)
0
6
0
Order By: Relevance
“…To confirm the role of these genes in TOR signaling of V. dahliae , we tested sensitivity of Δ gtr1 and Δ tsc2 to factors that induce autophagy and compared their phenotypes to that of the Δ atg1 mutant which is impaired in autophagy (Vangalis et al, 2021b). The ability of conidia to germinate in the absence of nitrogen sources was significantly reduced in all the deletion mutants compared to the wild-type strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm the role of these genes in TOR signaling of V. dahliae , we tested sensitivity of Δ gtr1 and Δ tsc2 to factors that induce autophagy and compared their phenotypes to that of the Δ atg1 mutant which is impaired in autophagy (Vangalis et al, 2021b). The ability of conidia to germinate in the absence of nitrogen sources was significantly reduced in all the deletion mutants compared to the wild-type strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their role in chemotropism, gtr1 and tsc2 were required for normal morphogenesis, physiology, and stress response, indicating a conserved role of the TOR signaling pathway in fungal development (Yu et al, 2014). The conidial germination defect of the Δtsc2 mutant could be attributed to its inability to undergo autophagy, a process that was shown to be important for conidial germination (Kikuma et al, 2006;Vangalis et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also showed that hematopoietic stem cell bias is regulated by the distinct niche they occupy in bone marrow [ 7 ]. Based on the bias, myeloid-biased (My-Bi), balanced (Ba), lymphoid-biased (Ly-Bi), platelet-biased (Pl-Bi), and quiescent Peroxisome Proliferator-Activated Receptor γ positive (PPARγ+) osteoclast-biased (Os-Bi) progenitors have been discovered ( Figure 1 ; [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]).…”
Section: Monocyte–macrophage Cell Lineagementioning
confidence: 99%
“…It was previously thought that heterokaryon formation is rare in nature due to heterokaryon incompatibility (HI), i.e., regulated cell death occurring at the place of fusion between the two hyphae of incompatible mycelia ( Glass and Dementhon, 2006 ; Daskalov et al, 2017 ; Gonçalves et al, 2020 ; Rico-Ramírez et al, 2022 ). Whilst this is not always the case ( Heller et al, 2018 ; Daskalov et al, 2019 ), evidence is accumulating that in spore germination phase, HI mechanisms may be relaxed or absent under different environmental conditions ( Roca et al, 2005 ; Ishikawa et al, 2012 ; Mehta and Baghela, 2021 ; Vangalis et al, 2021 ). Fusion of two mature colonies of incompatible strains of Colletotrichum lindemuthianum induces cell death, while conidial anastomosis tube (CAT) fusion generates a stable mycelium, capable of producing uninucleate conidia phenotypically different from the parents ( Ishikawa et al, 2012 ).…”
Section: Nuclear Genotype Heterogeneity and Dynamicsmentioning
confidence: 99%